Strategi Dakwah Kampung Qur’an Dalam Meningkatkan Nilai-Nilai Religius Di Desa Kalidilem Randuagung Lumajang - Aang Burhanuddin; Zainil Ghulam (Institut Agama Islam Syarifuddin Lumajang, 2020)
Religious activities in the village of Kalidilem are already running but there are still some residents, especially teenagers, who get drunk and promiscuity. To overcome this problem a Kampung Qur’an program is formed. Kampung Qur'an is one of the Nahdlatul Ulama (NU, Islamic Organization) Lumajang programs that synergizes with JQH in the form of a missionary institution tasked with spreading the message of da'wah with the Qur'an. The village of the Qur'an was fully surrendered to the NU Autonomous Agency in charge of al-Qur'an. In the process of da'wah an important thing to consider is the da'wah strategy. This research uses descriptive qualitative method, with a phenomenological approach. Data collection techniques using interviews, observation and documentation. The conclusion of this study is the da'wah strategy used by the Qur'an Village there are 5 namely: 1) Sentimental strategy: conducting regular recitation, giving advice with good words, such as calling mad'u as